Simulation of dynamic systems with MATLAB and Simulink - Klee, Harold (CRC Press, 2011)
"Employing the widely adopted MATLAB and Simulink software packages, this book offers the scientific and engineering communities integrated coverage of continuous simulation and the essential prerequisites in one resource. It also provides a complete introduction to the Real-Time Workshop. The text takes the reader through the process of converting a mathematical model of a continuous or discrete system into a simulation model and source code implementation, which can be explored to better understand the dynamic behavior of the system. The second edition addresses common nonlinearities, expands coverage of the Kalman filter, and features extensive treatment of numerical parameters"--